Tongue metastasis as an initial presentation of renal cell carcinoma - Petar Ðanić; Davorin Ðanić; Darko Macan (Medicinski glasnik, 2017)
Aim: Distal metastases to oral cavity are very rare. Adenocarcinoma, renal cell carcinoma (RCC) and squamous cell carcinoma are the most common metastatic tumours. The aim of this study was to assess the diagnostic relevance of metastatic renal cell carcinoma on tongue manifestations in large patient series. Methods: A patient with distal RCC metastases to the tongue and neck lymph nodes as the first manifestations of malignancy was presented. Also, all reports described during 106-year period relating to distal RCC metastasis to the tongue were evaluated. Results: In the presented patient, initial presentation of RCC was metastasis to the tongue. Three months after nephrectomy, tongue tumour resection and radical neck dissection were performed. Histopathological analysis confirmed RCC metastasis. Postoperatively, the patient underwent radiotherapy and polychemotherapy. Tongue metastasis from RCC is extremely rare with only 51 cases reported during the 106-year period. In only 7 patients tongue metastasis was reported as an initial presentation of RCC. Conclusion: The RCC metastasizing to the tongue is extremely rare and thus it poses a diagnostic challenge especially when it is the first sign of malignancy. Therapeutic decisions should maximize patient comfort and minimize morbidity considering the poor long-term prognosis.
Keywords: oral cavity; renal carcinoma; metastasis